Digital Sociopreneur untuk Pemberdayaan Masyarakat melalui Inovasi Komunikasi Pemasaran Digital di Kampung Cibayawak, Desa Pagelaran, Banten: Indonesia - Arianti, Gusmia; Zarkasi, Irwa Rochimah; Kulau, Febriansyah; Sunarmo; Haroni, Nanang; Hanafi, Des (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Digital transformation has opened up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their markets; however, limited digital literacy remains a major obstacle in many communities, including Cibayawak Hamlet, Pagelaran Village, Banten. This community service program is designed with the spirit of digital sociopreneurship by optimizing digital technology to create social value while empowering the local economy. Through the active involvement of young people, students, and lecturers, this program not only transfers technical skills but also fosters social awareness to help MSMEs advance in digital marketing. The focus of the activity is training in producing creative short video content for TikTok and improving product packaging design. Content quality evaluation was carried out using a 12-indicator validation sheet (scale 1–5) on seven videos created by participants. The results showed that ethical and legal compliance and audio/image quality were key strengths, while titles and captions, editing and transitions, and message sharpening still needed to be strengthened. This program emphasizes the role of young people as agents of digital change capable of bridging the technology gap at the community level. Practical recommendations such as storyboarding, keyword-based caption writing, and lightweight editing templates are offered as step-by-step solutions to help MSMEs produce content relevant to social media trends. With a digital sociopreneurial approach, this program not only enhances marketing skills but also builds a collaborative ecosystem between academics, young people, and local businesses for digital-based economic independence.